Crime Victims Support System and Restorative Justice: Possible Implementation in Malaysia - Azman, Azlinda; Mohammad, Mohd Taufik (Maryland Institute of Research, Center for Socio-Economic Research, 2012)
Victims’ position is increasingly acknowledged in the criminal justice system across the world. Because of that, criminal justice systems in various countries slowly transform from focusing too much on the relationship between offenders and the legal system and to between the offenders and their victims. Several programs are highlighted such as victim-offender mediation, family group conferences, reparative orders and referral orders in this article. Findings from several studies support the effectiveness of the programs on both the victims and the offenders in terms of several measurements such as satisfaction and recidivism. Looking at this revolution, Malaysian academicians and professionals are beginning to recognize restorative justice as a possible revolution to its criminal justice system, but Malaysian criminal justice system first needs to strengthen or build components that support victims of crime, as this is one of the main principles of restorative justice. Currently, Malaysia still focuses on offenders and their relationship with legal system, but not much with their own victims (physical, emotional, and psychological consequences of the crime). Several possible issues before formal implementation of restorative justice are discussed. The issues (culture, training, and attitude of Malaysian people, including the victims, offenders, and those who work with them) can influence the efficiency of restorative justice programs if not identified systematically. These issues can also be the possible research areas to be ventured in the future as these researches can help in implementation.